Developing Environment Geography Learning Through Machine Learning Media and Its Application at Rural-Urban School - Kurnianto, Fahmi Arif; Nurdin, Elan Artono; Pangastuti, Era Iswara; Riyanti, Novitasari Sudar (Future Science, 2024)
Environment geography has strong characteristics in combining classroom learning and in the field. Currently, machine learning development were designed to help several problem particularly in education. This study aims to evaluate the quality of Geographic Information System based machine in rural and urban school. Moreover, we also measured effect of GIS based machine learning towards learning outcome. We used quasi-experimental design to ensure the effect of GIS based machine learning media towards learning outcome. Moreover, we also used curriculum implementation index to ensure current curriculum implementation by teacher. Students were divided into 3 groups (2 experimental groups and 1 control group). The experimental group was treated by applying a guided inquiry model through GIS based machine learning media while the control group was treated by conventional models. The results show that the quality of learning by utilizing Geographic Information Systems is remain low which is indicated by low score at laboratory and media. However, in general curriculum implementation index showed moderate score 6.8, respectively. Moreover, results of quasi experiment design showed that GIS based machine learning has significant effect on students’ learning outcome which is represented by t-test score at 0.00, respectively. GIS based learning were able to enhance students’ learning outcome, meanwhile at current condition we found low index for laboratory and media aspect both in rural and urban school.